ISORA 2018 : Understanding Revenue Administration - Crandall, William (Departmental Papers; Departmental Paper ;, 2021)
The International Survey on Revenue Administration (ISORA) collects tax administration data from national or federal tax administrations. It surveys tax administration operations and other characteristics based on common questions and definitions agreed by four international organizations: the Inter-American Center of Tax Administrations (CIAT), the International Monetary Fund (IMF), the Intra-European Organisation of Tax Administrations (IOTA), and the Organisation for Economic Co-operation and Development (OECD). These four Parties signed a Memorandum of Understanding (MOU) governing the administration and management of this worldwide survey. This publication presents the results of the International Survey on Revenue Administration (ISORA) 2018, encompassing responses from 159 national or federal tax administrations spanning profile information, performance, and practices in fiscal years 2018 and 2019. For ISORA 2018, the ISORA Parties partnered with the Asian Development Bank (ADB) to provide assistance to its members who were participating in the survey.